2004
DOI: 10.1212/01.wnl.0000144281.38555.e3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors, incidence of MCI, and rates of progression to dementia

Abstract: In this population, among those who progressed to dementia, 60% progressed to AD and 33% to VaD. Vascular risk factors influence incident mild cognitive impairment and the rate of progression to dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
378
9
14

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(438 citation statements)
references
References 53 publications
37
378
9
14
Order By: Relevance
“…Of the studies having examined whole samples without gender stratification, a number of prospective studies found no significant associations with T-C, LDL-C, HDL-C, and TG (Reitz et al, 2005;Reitz et al, 2008;Solfrizzi et al, 2004;Teunissen et al, 2003;van den Berg et al, 2007). Solomon et al reported positive associations between midlife (but not late-life) T-C and cognitive decline in episodic memory and fluency (Solomon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies having examined whole samples without gender stratification, a number of prospective studies found no significant associations with T-C, LDL-C, HDL-C, and TG (Reitz et al, 2005;Reitz et al, 2008;Solfrizzi et al, 2004;Teunissen et al, 2003;van den Berg et al, 2007). Solomon et al reported positive associations between midlife (but not late-life) T-C and cognitive decline in episodic memory and fluency (Solomon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Setting The methods of the Italian Longitudinal Study on Aging (ILSA) and the 1st, 2nd, and 3rd survey data collection have been described in detail elsewhere (Solfrizzi et al 2004(Solfrizzi et al , 2006. A sample of 5,632 subjects aged 65-84 years, free-living or institutionalized, was randomly selected from the electoral rolls of eight Italian municipalities after stratification for age and gender.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical examination and laboratory analyses Cases of coronary artery disease (myocardial infarction or angina pectoris), type 2 diabetes mellitus, hypertension, stroke, and peripheral artery disease were identified with a two-phase procedure, utilizing clinical criteria described in detail elsewhere (Solfrizzi et al 2004; The Italian Longitudinal Study on Aging Working Group 1997). Each participant was administered a screening questionnaire, a series of brief screening tests to identify suspect cases of the above listed diseases for further investigation, and a clinical evaluation (phase 1).…”
Section: Methodsmentioning
confidence: 99%
“…46 Among the studies with cognitive impairment as a categorical end point (Table 2), 42,48 -61 those using a dichotomized test score 53,57 classified from 15% 53 to 50% 57 of the participants as cognitively impaired and reported positive associations with hypertension. Two studies 50,56 found no association of mild cognitive impairment with hypertension earlier in life. Studies with dementia, 48,52,54 AD, 42,49,51,52,54,55,58 -61 or VaD 49,54,59 as the end point demonstrated a significantly positive association with Ն1 blood pressure index, if follow-up started from middle age rather than old age.…”
Section: Longitudinal Cohort Studiesmentioning
confidence: 99%